ANALISIS POTENSI PEMBANGKIT LISTRIK TENAGA MINI HIDRO DI CATCHMENT AREA WADUK JATIGEDE - Sinta Berliana Sipayung; Amalia Nurlatifah; Bambang Siswanto (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Jatigede Reservoir is the second largest reservoir in Southeast Asia. The reservoir will function as a Hydro Power Plant (PLTA) with an installed capacity of 110 MW. In this research will be predicted the potential of PLTMH in Catchment Area of Jatigede Reservoir around Cimanuk Watershed until 2020. The data used in this research include monthly rainfall prediction data based on CCAM model output from 1998-2020. Rainfall data will be validated using TRMM rainfall observation data from 1998-2014. The CCAM output rainfall data is used as the input data of debit estimation and water level by the SWAT model. The estimated discharge data and water level will be used as a material for calculating power potential. Both CCAM modeling results, TRMM image, CRU, and station data show that the catchment area of ​​Jatigede Reservoir (DAS Cimanuk) has a monsoonal or maximum rainfall pattern in the DJF season and a minimum in the JJA season. The CCAM output data itself shows good performance in estimating monthly rainfall in the area as evidenced by the high correlation between CCAM and TRMM monthly rainfall at Leuwi Daun which reaches about 0.58 and CCAM-Station reaches 0.71. While in Leuwi Goong the correlation results are not much different and show good performance too. According to the ArcSWAT model, there was a decrease of about -2x10-6 m3 / month discharge in the catchment area of ​​Jatigede Reservoir. The decline is arguably not so significant that despite the decrease in rainfall, the potential power of PLTMH in the Jatigede Reservoir by 2020 is fixed. Potential power in Catchment Area Jatigede Reservoir itself ranges up to 50 MW.Keywords: PLTMH, rainfall, flow, power